Difference of Neutrophil-to-Lymphocyte Ratio, Monocyte-to-Lymphocyte Ratio, and Platelet-to-Lymphocyte Ratio in Patients with Non-Hodgkin and Hodgkin Lymphoma - Jones, Frenky; Oehadian, Amaylia; Marthoenis, Marthoenis; Mersiana, Lusi (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Malignancy and inflammation are strongly connected. The inflammatory processes play a significant part in the development of lymphoma. Neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-lymphocyte ratio (PLR) can be used as potential biomarkers of inflammation in lymphoma. This study aimed to discover the differences between NLR, MLR, and PLR in patients diagnosed with non-Hodgkin lymphoma (NHL), and Hodgkin lymphoma (HL). Methods: This study employed a retrospective design using data from the lymphoma registry at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from 2020 to 2023. Sampling was carried out consecutively. Hematological data of patients with NHL and HL before chemotherapy were collected. The variance between the two groups was examined utilizing the Mann-Whitney U test.Results: In total, 122 data of patients were included, consisting of 75% NHL patients and 25% HL patients with a median age of 54 years (IQR 43–62). The overall NLR, MLR, and PLR tended to be lower in nHL than in HL patients although the differences were not statistically significant; with NLR 2.7 (0.7 – 12.2) vs. 3.2 (1.1 – 10.8) p=0.287, MLR 0.36 (0.04 – 1.86) vs. 0.46 (0.09 – 1.78) p=0.150, and PLR was 160.6 (20.2 – 1533.3) vs. 211.2 (50.6–1156.3) p=0.189, for NHL and HL, respectively.Conclusion: The lower values of NLR, MLR, and PLR in NHL indicate lower systemic inflammatory status in NHL than HL patients. Further studies are needed to evaluate dynamic changes of these biomarkers during treatment.